Incentive mechanism for promoting farmers to plant green manure in China. (10th September 2020) - Li, Fuduo; Ren, Jing; Wimmer, Stefan; Yin, Changbin; Li, Zhongyi; Xu, Changxu
Abstract: The Green Manure Planting Program (GMP), which is a typical case of payment for farmland ecosystem services, has come into play on conserving paddy fields in China. This paper analyses farmers' willingness to accept (WTA) for adopting GMP by employing the contingent valuation method (CVM) and Double-hurdle (D-H) model on the basis of a sample data set containing information on 1217 farmers in five provinces in southern paddy fields region (SPF) of China. The results show that farmers' WTA for adopting GMP was 3323 CNY/ha per year, which is much higher than the current compensation standards (com-standards) in the study region. This result explains why the current policy does invalidly stimulate farmers for adopting GMP. Farmers' WTA is not only influenced by the cost-benefit effect of GMP adoption, but also impacted by their perceived environmental value in improving the quality of paddy fields as well as the demographic and socioeconomic information such as farmers' age, political identities, income and paddy field area. It is costly if the government compensates all farmers who adopt GMP, letting farmers aware of more environmental value of GMP and maximally promoting the transformation of these environmental values into economic benefits is an effective measure to encourage them to adopt GMP.The results of this study can guide policy makers in determining the budget for GMP compensation and designing systematic compensation mechanism hence improve the sustainability of paddy fields conservation. Graphical abstract: Image 1 Highlights: The increased cost of adopting Green Manure Program (GMP) reduces farmers' enthusiasm to conserve paddy fields. Farmers' WTA of adopting GMP was 3323CNY/ha per year. Farmers with higher awareness of environmental value are more likely to adopt GMP with less compensation. Excessive government regulation will lead to a higher eco-compensation for GMP.